Cost-effectiveness of edaravone dexborneol sublingual tablet versus concentrated solution for injection for the treatment of acute ischemic stroke in China - Xie, Fan; Lu, Yuqiong; Yang, Zhuo; Zhang, Yanlei; Bao, Yujin; Lu, Yun (Frontiers in Pharmacology, 2025)
BackgroundEdaravone dexborneol sublingual tablet (EDSL) is a novel therapy for acute ischemic stroke (AIS), proven effective and safe. Its convenient dosage form also provides an alternative administration option, helping to enhance treatment accessibility. This study evaluates the cost-effectiveness of EDSL versus edaravone dexborneol concentrated solution for injection (EDCSI) from the Chinese healthcare system perspective.MethodsA combination of the short-term decision tree and long-term Markov model was constructed. Clinical data were derived from the TASTE-SL and TASTE trials. To adjust for baseline characteristics between the two treatment groups, stabilized inverse probability of treatment weighting (sIPTW) was applied, and both Average Treatment effect on the Treated (ATT) and Average Treatment Effect (ATE) weighted results were calculated to enhance comparability. Model parameters were extracted from published literature, public databases, and expert interviews. Sensitivity and scenario analyses were conducted to demonstrate the robustness of the base-case results.ResultsThere was no statistically significant difference in the proportion of patients achieving mRS score ≤1 between the EDSL and EDCSI groups after sIPTW (ATT: 71.8% vs. 67.6%; ATE: 69.3% vs. 64.6%). Notably, EDSL showed clear cost-effectiveness advantages, with an incremental cost-effectiveness ratio (ICER) of -¥2,089.84 per QALY gained. All sensitivity and scenario analyses confirmed the robustness of the base-case findings.ConclusionEDSL represents a more cost-effective therapy for AIS patients compared to EDCSI, offering comparable efficacy at a lower drug cost. A full 14-day treatment course may help maximize patient benefits.